Depresión y ansiedad en adolescentes del Coelgio Calasanz de Loja mediante la herramienta 23 del Ministerio de Salud Pública - Cosíos Sarmiento, Andrea Gabriela (2014)
Depression and anxiety coexist as a disease determined suicidal adolescents. This research aims to: make the tool 23 through early diagnosis of depression and anxiety in adolescents; investigate the main social risk factors focused on schooling that predispose adolescents to develop depression and anxiety; socialize with members of the medical department, teachers and teens about the results and the reality of depression and anxiety in the Education Unit Calasanz. It is a quantitative and qualitative descriptive study whose field are students who are enrolled in high school with a total number of 386 students, the tool 23 of the Ministry of Public Health of Ecuador employment. The time required for the completion of this investigation was a year between November 2013 and October 2014. Upon completion of this investigation the results guide us that within the school there is a 20% anxiety and 5% depression, and those with risk factors (physical abuse, discrimination) to develop these diseases are 4% of the high school students. Keywords: Depression, anxiety, tool 23